Stability Analysis for a Fractional-Order Coupled FitzHugh–Nagumo-Type Neuronal Model - Oana Brandibur; Eva Kaslik (Fractal and Fractional, 2022)
The aim of this work is to describe the dynamics of a fractional-order coupled FitzHugh–Nagumo neuronal model. The equilibrium states are analyzed in terms of their stability properties, both dependently and independently of the fractional orders of the Caputo derivatives, based on recently established theoretical results. Numerical simulations are shown to clarify and exemplify the theoretical results.